Penilaian Etika Homosentris Masyarakat Pesisir Desa Langgula Kecamatan Batudaa Pantai - Pontoiyo, Fuad; Hamidun, Marini Susanti; Panai, Abdul Haris; Rahim, Sukirman (Program Vokasi UNG, 2025)
Homocentric ethics place humans at the center of moral value, where the utilization of natural resources is often viewed solely from the perspective of human interests. This study aims to analyze the extent to which the principles of homocentric ethics are reflected in the behavior of the fishing community in Langgula Village, Batudaa Pantai District, as well as to evaluate their knowledge and awareness regarding coastal environmental conservation efforts. The research uses a mixed-method approach, including literature review, field interviews, and data visualization analysis using VOSviewer. The results show that the community has a fairly high ecological awareness, as seen through the determination of fishing seasons, coral reef preservation, and the use of local technologies such as squid attractors and bioreeftek to support sustainable aquaculture. The literature analysis also reveals that environmental ethics topics are often associated with issues of humanity, technology, and sustainable development. These findings indicate that community practices are not entirely based on homocentric principles but have shown a tendency toward ecocentric ethics. This study recommends a community-based approach in conservation planning and emphasizes the importance of integrating local and scientific knowledge as a foundation for sustainable coastal environmental policy